Ciliated Carcinoma Associated With Human Papiloma Virus: Presentation As Cervical Metastasis Of Unknown Primary. (28th October 2020) - Ibarra, A; Las Heras, F; Antonio, L; Montero, P; Besa, P; Henriquez, J; Labra, Y
Abstract: Introduction/Objective: There is a significant increase in high-risk human papilloma virus (HPV) -related carcinomas of the head and neck. Half of them debut with metastases in cervical nodes, of expansive growth, usually cystic-necrotic. Most are oropharyngeal primaries. They are non-keratinizing squamous carcinomas with mild atypia, sometimes with exceptional characteristics, such as glandular differentiation and inclusion of ciliated cells Methods: Clinical Case: 39-year-old male patient, operated two years ago, in another institution, for cervical metastasis from HPV-related Ciliated Carcinoma (HPV-RCC), 4.5 x 2 cm. No primary cancer was found in his study. Two months ago, a new 4.3 x 2.7 cm metastasis was resected, performing a right cervical dissection, with another 36 lymph nodes without tumor. Palatine tonsils, adenoids are removed and a biopsy of the oral mucosa is taken, and no malignancy was found. In our center, biopsies of the tongue and right glosso-tonsillar fold are taken, without objectify malignancy. Results: The metastases had macroscopic cystic-necrotic appearance. Histology corresponded to nonkeratinizing squamous carcinoma with microcystic spaces and the presence of ciliated columnar cells. The immunohistochemical study gave strong and diffuse positivity for p16. The real-time multiple PCR study detected HPV genotype 16. Conclusion: We present an exceptional case of Ciliated Carcinoma Related to HPV, a recently described entity. These are nonkeratinizing squamous neoplasms, which include cystic spaces and ciliated columnar cells. Both components reveal HPV positivity, with p16 expression and high-risk viral typing. HPV-RCC should be considered in the differential diagnosis of well-differentiated squamous lesions of the oropharyngeal cavity and at the cervical level, with non-neoplastic cysts. Our patient will undergo radiotherapy protocol, for unknown primary